Candidal endophthalmitis: a manifestation of systemic candidiasis. Issue 741 (July 1987) - Patel, B. C.; Kaye, S. B.; Morgan, L. H.
Abstract : Two patients on total parenteral nutrition who developed endophthalmitis secondary to Candida albicans are described. Candidal endophthalmitis as a manifestation of systemic candidiasis is discussed and its early diagnosis by bedside fundal examination in patients at risk is stressed.